Renewal Challenges To The Product Development Level Of Rural Banks - Markus Doddy Simanjuntak; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Pusat Riset dan Inovasi Nasional, 2022)
Rural Banks has a very big opportunity in its development in the future, especially seen from the increasing people's financial market in Indonesia. Rural Banks make a means of financial needs in the management of households, both to overcome basic risks and risks to the assets owned. This research discusses in depth the challenges to the development of Rural Banks in Indonesia and discusses the opportunities and challenges of product modification in Rural Banks in Indonesia. This research uses library research or commonly called literature review, relying on a descriptive approach. The data used is in the form of writing, words, pictures, and there is no element of numbers. The results of the research explain that the challenges to the modification of people's products in Indonesia are caused by several things including the global economic downturn, the state of people who are unfamiliar with Rural Banks, inadequate resources and lack of capital.